Dampak Game Online terhadap Akhlak Remaja di Era Digital di Desa Sidoasri Kecamatan Sumbermanjing Wetan - Saiful Basori; Zainuddin Fanani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the impact of online games on the moral development of adolescents in Sidoasri Village, Sumbermanjing Wetan District, Malang Regency. Amid the rapid advancement of digital technology and the widespread access to smartphones and the internet, online gaming has become an integral part of daily life, including among rural youth. Using a descriptive qualitative approach, this research combines literature review and field studies through observations and interviews with adolescents, parents, and teachers. The findings reveal that online gaming has dual impacts on adolescent morality. Negative effects identified include decreased adherence to social norms, increased verbal aggression, reduced social empathy, and neglect of moral responsibilities and religious obligations. On the other hand, moderate and supervised game usage shows positive outcomes such as improved critical thinking skills, teamwork, creativity, and proficiency in foreign languages and information technology. These results highlight that the impact of online games greatly depends on the type of game, frequency of use, influence of the social environment, and the level of parental and educational supervision. Therefore, a holistic and contextual character education approach is necessary, incorporating digital literacy based on moral and religious values into the lives of adolescents, especially in socially and religiously diverse areas like Sidoasri. This study recommends a collaborative effort between families, schools, communities, and the government to shape a digitally literate yet morally grounded young generation.